Affinographs a dynamic method for assessment of individuals, couples, families, and households - Jedlicka, Davor; SpringerLink (Online services). (New York Springer, 2011)
Affinographs A Dynamic Method for Assessment of Individuals, Couples, Families, and Households Davor Jedlicka The word family traditionally referred to two parents and their children, a concept that has been subject to constant revisiting over the past half-century with society's gradual  acceptance of single-parent, blended, adopted, and same-sex families. And as the relationships increase in complexity, so do their problems, requiring innovative professional tools for understanding and assessing families. Affinographs expand on the genogram and other methods currently in use by translating complex family narratives into dynamic, gender-neutral graphic images. Affinograph explains how to create and use these images to generate hypothesis for clinical interventions. The affinographs  represent relationships as clients see them (such as having more than two parents). The book offers varied uses of the method in working with troubled families over diverse situations and across the helping disciplines. Case studies illustrate compound families formed through serial marriages, multiple generations, and multiple households. Extramarital relationships, from the briefest  to the most committed, are also examined. The book covers: Constructing the affinograph. Charting patterns of divorce and remarriage. Assessing gay and lesbian families. Using affinographs in family therapy. Applying affinographs to child protection work. Integrating affinographs into genealogy. Family therapists, sociologists, psychologists, counselors, social workers, and others who provide services to families will find Affinographs both highly informative and eminently useful. The book also lends itself to research and teaching application
Introduction: What is an Affinograph?- Why Affinographs?-Constructing Affinographs -- Critical Issues in Protecting Children and Servicing Families -- Patterns of Divorce and Remarriage -- An Affinograph Method of Assessing Same Gender Couples -- Affiars and Ephemeral Relations with Lasting Consequences -- Focused Affinographs in Family Therapy -- Affinology: The Affinograph Method for Genealogy -- Future of the Affinograph.
Electronic reproduction.
Keywords: Interpersonal relations; Families; Family assessment; Electronic book